2020
DOI: 10.1002/jclp.23046
|View full text |Cite
|
Sign up to set email alerts
|

Moderating effects of dysregulation and fear of positive emotions on the relationship between posttraumatic stress disorder symptoms and positive memory count

Abstract: Objectives We examined moderating effects of positive emotion dysregulation and fear of positive emotions in the relation between posttraumatic stress disorder (PTSD) severity and positive memory count. Method Participants were 205 trauma‐exposed community individuals (Mage = 35.44; 61.50% female). Results Moderation analyses indicated interaction effects of PTSD severity with nonacceptance of positive emotions (b = −0.01, p = .002) and difficulties with goal‐directed behaviors when experiencing positive emoti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 17 publications
(21 citation statements)
references
References 123 publications
(156 reference statements)
2
17
0
Order By: Relevance
“…Recent research has shown that greater PTSD severity is associated with fewer specific positive memories when individuals reported more non-acceptance of positive emotions and more difficulties engaging in goal-directed behaviours in the context of positive emotions (Contractor, Weiss, & Forkus, 2021). Further, in a sample of trauma-exposed community participants, positive emotion dysregulation was a significant predictor of fewer retrieved positive memories, controlling for PTSD severity (Dolan et al, 2020).…”
Section: Heterogeneity In Affective Processes Following Positive Memo...mentioning
confidence: 93%
See 1 more Smart Citation
“…Recent research has shown that greater PTSD severity is associated with fewer specific positive memories when individuals reported more non-acceptance of positive emotions and more difficulties engaging in goal-directed behaviours in the context of positive emotions (Contractor, Weiss, & Forkus, 2021). Further, in a sample of trauma-exposed community participants, positive emotion dysregulation was a significant predictor of fewer retrieved positive memories, controlling for PTSD severity (Dolan et al, 2020).…”
Section: Heterogeneity In Affective Processes Following Positive Memo...mentioning
confidence: 93%
“…Indeed, research indicates that trauma‐exposed individuals with PTSD symptoms exhibit dysregulation of positive emotions; they are non‐accepting of positive emotions and have difficulties controlling impulsive behaviours and engaging in goal‐directed behaviours when experiencing positive emotions (Weiss et al, 2018; Weiss, Contractor, Forkus, et al, 2020; Weiss, Contractor, Raudales, et al, 2020; Weiss, Nelson, et al, 2019). Recent research has shown that greater PTSD severity is associated with fewer specific positive memories when individuals reported more non‐acceptance of positive emotions and more difficulties engaging in goal‐directed behaviours in the context of positive emotions (Contractor, Weiss, & Forkus, 2021). Further, in a sample of trauma‐exposed community participants, positive emotion dysregulation was a significant predictor of fewer retrieved positive memories, controlling for PTSD severity (Dolan et al, 2020).…”
Section: Heterogeneity In Affective Processes Following Positive Memo...mentioning
confidence: 99%
“…Evidence indicates that trauma-exposed individuals with PTSD symptoms do not accept positive emotions and have difficulties controlling impulsive behaviors and engaging in goal-directed behaviors when experiencing positive emotions (Weiss et al, 2018). Recent research has shown that PTSD severity is associated with fewer retrieved positive memories when individuals report nonacceptance of positive emotions and difficulties engaging in goal-directed behaviors in the context of positive emotions (Contractor, Weiss, & Forkus, 2021). Broadly, this lack of sustained positive affect may contribute to more PTSD severity over time.…”
mentioning
confidence: 99%
“…Emerging evidence indicates that the etiology and exacerbation of PTSD symptoms is associated with deficits in positive memory retrieval (Bryant et al, 2007; Contractor et al, 2018; Hauer et al, 2009). Yet, there is a limited understanding and examination of factors that may influence this relation (Contractor, Weiss, et al, 2021). A variable worth investigating is sleep difficulties, given that short sleep duration and poor sleep quality are associated with both PTSD (Germain, 2013) and memory processes (reviewed in Walker & Stickgold, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…Beyond traumatic memories, positive memory retrieval difficulties relate to PTSD's etiology, maintenance, and severity (Bryant et al, 2007; Contractor et al, 2018; Contractor, Greene, et al, 2020; Hauer et al, 2009). Perhaps, biased attention toward negatively valenced information (Fani et al, 2012), a tendency to focus on negative and traumatic memories (Sutherland & Bryant, 2005), and emotional numbing and dysregulation processes (Contractor, Weiss, et al, 2021; Litz et al, 2000) may contribute to difficulties retrieving specific positive memories among trauma‐exposed individuals with PTSD symptoms (Sutherland & Bryant, 2005; Wingenfeld et al, 2013).…”
Section: Introductionmentioning
confidence: 99%